Master of the phantom isle - Mull, Brandon, 1974- (Mull, Brandon, 1974- Dragonwatch (Series), 2019)
As the evil Celebrant conquers more and more dragon sanctuaries, Kendra must raise an army of friends and allies on her own to fight him because her brother Seth and Bracken are missing.